Advances in Doppler optical coherence tomography and angiography. Issue 1 (30th December 2019) - Li, Yan; Chen, Jason; Chen, Zhongping
Abstract: Since the first demonstration of Doppler optical coherence tomography (OCT) in 1997, several functional extensions of Doppler OCT have been developed, including velocimetry, angiogram, and optical coherence elastography. These functional techniques have been widely used in research and clinical applications, particularly in ophthalmology. Here, we review the principles, representative methods, and applications of different Doppler OCT techniques, followed by discussion on the innovations, limitations, and future directions of each of these techniques. Abstract : Doppler OCT and OCT angiography are a noninvasive imaging technology that visualizes and quantifies microvasculature as well as elasticity in vivo. These functional techniques have brought significant impact on disease diagnostics and management of ocular disorders that lead to blindness, including macular degeneration, glaucoma, and diabetic retinopathy. Potential utilities in cancer diagnosis and brain function have also been demonstrated, providing a powerful tool for basic research and clinical applications.